Analysis of Financial Performance By Methods Economic Valueadded (Eva) at PT. Argha Karya Prima Industry Tbk - Dwi Anugerah Lestari Musa; Welimas Kristina Parinsi; Kartika Septiary Pratiwi Musa (Journal of Innovative and Creativity, 2026)
This study aims to analyze the financial performance of PT Argha Karya Prima Industry, Tbk in 2019-2022 using the economic value added (EVA) method. This research is descriptive research with a quantitative approach. The population in this study is the annual financial report of PT Argha Karya Prima Industry, Tbk. The sample of this study is the financial position report and comprehensive income statement of PT. Agha Karya Prima Industry, Tbk 2019-2022. The results of this study indicate that, the performance of PT Argha Karya Prima Industry, Tbk in 2019-2020 EVA value> 0, then there is added value and the Company's financial performance is good. Meanwhile, in 2021-2022 the EVA value <0, then there is no added value and the Company's financial performance is not good. Overall, it can be said that in the last 4 years we can judge that there is no economic added value. Thus, it can be said that PT Argha Karya Prima Industry, Tbk for the 2019-2022 period is unable to create economic added value for owners of capital or shareholders, meaning that its financial performance is not good.